Redes de Bragg para aplicações em sensoriamento e telecomunicações - Coradin, Francelli Klemba (2011)
This work presents the production of fiber Bragg gratings with different profiles for application in sensing and in telecommunications. The gratings for sensing application were recorded using direct illumination of a phase mask as well as a phase mask interferometer, at the Federal University of Technology - Parana. The gratings were recorded in hydrogen loaded standard telecommunication fibers and photosensitive fibers using a Nd: YAG laser (Tempest-20, New Wave) at 266 nm and a KrF excimer laser at 248 nm (Xanto XS-Coherent). Experiments were performed in order to reach the thermal stabilization of the devices using a laboratory oven, where the gratings were submitted to thermal cycles which included both annealing and quenching. Tests to determine the maximum operating temperature of the produced fiber Bragg gratings were also performed. Refractometric sensors were produced by wet-etching of the fiber optic cladding using hydrofluoric acid and employed in the analysis of water-ethanol mixture. Two etched fiber Bragg gratings operating close to 1300 nm and 1500 nm were used in the experiment. Four configurations for the refractometric sensor were studied, in dual-wavelength and single-wavelength operation modes, and at two sample temperatures. Calibration curves were determined for the range between 0.0 and 100.0 % v/v of ethanol in water, and the sensor performance for each configuration was analyzed by comparing its sensitivity, conformity, repeatability and combined uncertainty. The gratings for the application in telecommunications were recorded in photosensitive fibers with direct illumination of phase mask at the Institute of Telecommunications of the Aveiro University, in Portugal. Chirped fiber Bragg gratings were produced with the use of an excimer laser operating at 248 nm (S-industrial BraggStar LN) and with the use of translation stages with maximum resolution of 1 nm. The study of Bragg grating spectral evolution with the writing energy allowed the project of devices with predefined characteristics.